Basic Life Support Training for Autonomous Organizations (Ortom) Muhammadiyah - Ida Rosidawati; Hana Aryani; Hisyam Farhan; Ihnatul Fauziah; Widy Andriana; Dera Trisna (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Emergency events certainly cannot be predicted, whenever and wherever someone can experience it, the event requires immediate help. Delays in handling can result in physical disability or even death. This condition requires proper and immediate emergency treatment, so that first aid in victims / patients can be done optimally. The role of the community in first aid to health problems has been widely felt and in general who find the first time emergency patients at the scene is a community known as "lay people", so they are the ones who often provide first aid to patients before by competent health workers. This condition becomes a shared responsibility, especially Muhammadiyah Regional Leader (PDM) and Colleges as organization that pay attention to health services and to the community. The solution offered is the implementation of basic life support training. The activity was held on November 24, 2021 with the target of Muhammadiyah Autonomous Organization (ortom) in Tasikmalaya City. The implementation of activities carried out by lecturers and students is assisted by PDM Tasikmalaya City.